POTENSI STREPTOMYCES ENDOFIT RIMPANG KENCUR DAN DAUN SIRIH MERAH SEBAGAI ANTITUBERKULOSIS PADA MYCOBACTERIUM TUBERCULOSIS GALUR SENSITIF - Siti Nur Azizah, Mikhania Cristiningtyas Eryani (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2019)
The objective of this research was to obtain Endophitic Streptomyces from some medical plants which have antituberculosis effect and also to test its antitubercullosis activity againts sensitive stain of Mycobacterium tuberculosis. Medicinal plants used in this study were Kaemferia galanga, Hibiscus sabdariffa and Piper cronatum. Streptomyces was isolated using two different media namely Humic Acid Vitamin (HV) agar and HV with plant extract, and purified on Yeast Malt Agar (YMA) medium. Morphological characterization of Streptomyces obtained was observed including aerial mycelium and substrate mycelium, pigmentation, and colony surface. A total of 5 endophitic Streptomyces genus were obtained from medicinal plant. Isolates K.J3A, K.J3B, K.J4 and K.J11 from Kaemferia galanga radix, S.MJ1 from Piper cronatum folium. Streptomyces was not found from Hibiscus sabdariffa calyx. Each isolate had variety of characteristics which could be seen in aerial mass color, substrate mass color, and pigmentation. Antitubercullosis activity showed that total of 5 endophitic Streptomyces were not capable to inhibit the growth sensitive stain of M. tubercullosis.Keywods: Antituberculosis, endophitic actinomycetes, Kaemferia galanga, Hibiscus sabdariffa